824 Case Series on the Use of Volume Assured Pressure Support in Patients with Chronic Pulmonary Disease and Progressive Hypercapnia. (3rd May 2021) - LeMaster, William; Jun, Dale; De Cruz, Sharon; Zeidler, Michelle; Saggar, Rajan
Abstract: Introduction: Chronic hypercapnia results from destruction of lung parenchyma which occurs in chronic lung diseases including interstitial lung disease (ILD), bronchiectasis, and chronic lung transplant rejection. Many patients with these diseases will experience progressive respiratory failure eventually requiring consideration of transplantation or re-transplantation. Due to physiologic changes in sleep including reduction in tidal volume, worsening air tapping, and REM atonia, hypoventilation can be exacerbated during the sleeping hours. We present four patients who were prescribed nocturnal Volume Assured Pressure Support VAPS for their progressive hypercapnia. Report of case(s): Subject 1 is a 72 year old female with severe bronchiectasis and restrictive lung disease due to TB pneumonia at a young age. Subject 2 is a 45 year old male with history of pulmonary cavitation due to extensive TB disease when he was younger. Subject 3 is a 45-year-old woman with rheumatoid arthritis related ILD with associated pulmonary arterial hypertension. Subject 4 is a 74 year old patient with a bilateral lung transplant for IPF complicated by bronchiolitis obliterans syndrome who presented with progressive dyspnea and hypercapnia. Despite optimal therapy, all of these patients were admitted for hypercapnic and hypoxemic respiratory failure requiring treatment with BPAP then transitioned to nocturnal VAPS on discharge. For all patients, dyspnea and pCO2 improved as outpatients although all patients did eventually experience an exacerbation of their lung disease requiring repeat admission. Conclusion: Due to the physiologic changes that occur with sleep, patients with severe lung disease may experience worsening CO2 retention while sleeping. There is little data assessing the use of chronic nocturnal non-invasive ventilation (NIV) to treat the hypercapnia of chronic lung diseases other than chronic obstructive pulmonary disease, extra-thoracic restriction, and neuromuscular disease. In this case series, nocturnal VAPS stabilized and/or reduced pCO2 in patients with pulmonary parenchymal disease of various etiologies. Additional studies are needed to assess long term effects of VAPS in these patients, including exacerbations, symptoms, and overall mortality. Support (if any):